Improvement in histology, enzymatic activity, and redox state of the liver following administration of Cinnamomum zeylanicum bark oil in rats with established hepatotoxicity - Niknezhad, Fatemeh (Anat Cell Biol, 2019)
Formaldehyde (FA) is an environmentally-available pollutant. Since the liver acts as a detoxifier in the human body, it is the first and most affected organ in individuals exposed to higher-than-normal amounts of FA. FA mainly alters oxidant/antioxidant status and initiates oxidative stress, and by means, causes functional damage to the liver. Thus, it is important to identify natural bioactive compounds with antioxidant properties in order to be used as food additives. Cinnamon (Cinnamomum zeylanicum) is a popular flavor and also a medicinal plant with a variety of beneficial effects. In the present original study, cinnamon essential oil (CEO) has been administrated at doses of 10, 20, and 100 mg/kg, orally, to hepatotoxicity rat models caused by FA (10 mg/kg, intraperitoneally). Liver enzymes and its histology were assessed and oxidative stress biomarkers in the liver tissue were also examined. CEO administration caused a significant increase in superoxide dismutase, glutathione peroxidase, and catalase and a prominent decrease in nitric oxide levels in the liver tissue. Also, in serum samples, CEO significantly reduced the elevated amounts of alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase. When assessed histologically, portal area and central vein fibrosis alongside with the hepatocytes' hypereosinophilia and swelling, focal inflammation, and necrotic areas were found to be prominently decreased in the CEO group. In conclusion, our study suggested that the CEO may have the potential for being used against FA-induced hepatotoxicity.